2018
DOI: 10.1002/asia.201800697
|View full text |Cite
|
Sign up to set email alerts
|

Cp*CoIII‐Catalyzed Efficient Dehydrogenation of Secondary Alcohols

Abstract: A novel, well-defined molecular Cp*Co complex was isolated and structurally characterized for the first time. The efficiency of this cobalt catalyst was demonstrated in the alcohol dehydrogenation and dehydrative coupling of secondary alcohols under mild conditions into ketones and ethers, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…The precatalyst 3 has been fully characterized, including by an X-ray structural analysis, as a diamagnetic compound. 26 In agreement with the experimental evidence, the calculations on the model system indeed indicate a slight preference for the singlet state s-V (singlet-triplet gap of 0.3 kcal/mol for E and 0.2 kcal/mol for G with solvent correction in toluene at 25°C). The comparison of the optimized structure with that determined by X-ray diffraction is also excellent (see SI, section S4).…”
Section: (C) Alcohol Dehydrogenation With [Cpcoi(oquin)]/tbuoksupporting
confidence: 83%
See 1 more Smart Citation
“…The precatalyst 3 has been fully characterized, including by an X-ray structural analysis, as a diamagnetic compound. 26 In agreement with the experimental evidence, the calculations on the model system indeed indicate a slight preference for the singlet state s-V (singlet-triplet gap of 0.3 kcal/mol for E and 0.2 kcal/mol for G with solvent correction in toluene at 25°C). The comparison of the optimized structure with that determined by X-ray diffraction is also excellent (see SI, section S4).…”
Section: (C) Alcohol Dehydrogenation With [Cpcoi(oquin)]/tbuoksupporting
confidence: 83%
“…The high-valence organometallic cobalt system Cp*Co III is an active catalyst for the hydrogenation of CO 2 and carbonates, as well as for the dehydrogenation of ammonia borane and secondary alcohols . It was also shown to promote a family of organic transformations that involve borrowing hydrogen chemistry. The observation of a peculiar superior performance and selectivity of an electronically saturated complex for the alkylation of a ketone by secondary alcohols, as detailed in the next section, has caught our attention and has motivated us to explore the detailed mechanism of alcohol dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the work of Hong, [29] Werner and de Vries, [30]] and our earlier results on transfer hydrogenation of ketones using group 9 metals, [31a,34] we intend to execute transfer hydrogenation of carbonate into diol using isopropanol as liquid organic hydrogen carrier agent. To our delight, using same conditions established for hydrogenation was extended for transfer hydrogenation of cyclic carbonate 1 c into diol ( 2 c ) in 87 % isolated yield with 1 mol% of cobalt(III) ( C ) using 2‐propanol using as a hydrogen source as shown in Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Gangwar and co‐workers reported synthesis of an air‐stable, phosphine/privileged pincer ligand‐free cobalt (III) complex based on Cp* ligand 72 and its catalytic activity in dehydrogenation of secondary alcohols under mild reaction conditions into ketones (Scheme 50). [70] This catalytic system were also applied for the dehydrative etherification.…”
Section: Phosphine‐free Ligand Systems Complexation and Applications ...mentioning
confidence: 99%